Pengaruh Digital Marketing, Influencer Marketing, dan Online Customer Review Terhadap Keputusan Pembelian Online Shop di Soloraya - Muhammad Rivaldo Darmawan; Moechammad Nasir (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
Technology drives human attitudes and behavior, technological changes can also have an impact on the creation of new market share. With the support provided by technological changes, researchers want to assess the influence of digital marketing, influencer marketing and online customer reviews on customer purchasing decisions on online shop platforms in Solo Raya. The study was conducted in Solo Raya using a purposive sampling method distributed through questionnaires as a place to collect data, data was then obtained from 200 respondents. Furthermore, the data was processed using the Partial Least Square test using SmartPls 3.0 which obtained the results that digital marketing, influencer marketing and online customer reviews can have a high and positive influence on customer purchasing decisions with an R-Square influence value of 81.5%.